Diseño vial y comparación técnico económica entre pavimento flexible (asfaltico) y pavimento semiflexible (adoquinado) para la urbanización los pinos ubicada en la parroquia Cutuglahua cantón Mejía provincia Pichincha. - Lozada Moya, José Andrés (2018)
The following Project has necessary studies in order to carry out designs for road structure for LOS PINOS urbanization and also presents an análisis of surfacing alternatives such as flexible pavement (asphalt) and jointed pavement (cobblestone) , which will be selected according to quality, economy and maintainance. For the purpose of getting the structural designs of these two presented alternatives in the Project , field information was gathered such as topographical rises, soil study samples, traffic counting and the information was processed With the gathered information, the corresponding studies are done such as traffic studies through which the equivalent axle number ESAL´S is determined. Fundamental parameter to pavement design, geometrical road design for the urbanization, geotecnical road design in which the characteristics of the subgrade is presented. The structural road design will be carried out applying the AASHTO 93 method. Also, for both surfacing types, hydrological study and drainage design according to INEM rules were done, environmental impact. Finally, a technical economic análisis is carried out to determine the pavement alternative of the best characteristics about quality, economy and maintainance which will be done according to Budget, outcomes, incomes, maintainance cost and viability